Public Understanding of Land Conflicts through Strengthening Land Rights Certificates in Sukmajaya Subdistrict, Depok City - Abdullah, Ali; Suwarsit; Arifardhani, Yoyo (International Journal of Community Service (IJCS), 2025)
This study examines public understanding of land conflicts through strengthening land title certificates in Sukmajaya Village, Depok City. Using a qualitative approach with a case study design, this study involved 200 respondents and various related stakeholders. The results of the study showed a significant increase in public understanding of the importance of land title certificates, from an average of 40% in 2022 to more than 85% in 2024. The land title strengthening program succeeded in reducing land conflicts from 45 cases to 18 cases, with a resolution rate of 83.3%. Economically, this program increased asset value by 48.6% and credit access by 134.1%. The percentage of certified land increased from 50% to 90% in three years. The land management model developed has proven effective and has the potential to be replicated in other areas, while still paying attention to strengthening the digitalization system of administration and developing human resource capacity.